Comparison between traditional and new obesity measurement index for screening metabolic associated fatty liver disease - Wang, Hongyan; Zhang, Yuxue; Liu, Yupeng; Li, Hui; Xu, Ruiling; Fu, Hongmei; Yan, Chaoqi; Qu, Bo (Frontiers in Endocrinology, 2023)
Objectives Obesity measurement indexes have certain screening value for metabolic diseases. To investigate associations between metabolic associated fatty liver disease (MAFLD) and obesity measurement indexes, including traditional indexes (BMI, WC, WHtR) and new indexes (ABSI, BRI, VAI, LAP), and assess their screening ability. Methods 12,658 subjects aged 18-75 at the Health Center of a Class III Grade A Hospital were included, who were divided into MAFLD and non-MAFLD groups. Spearman’s rank correlation was used to study the correlation between MAFLD and obesity measurement indexes. Receiver operating characteristic (ROC) curves were used to calculate the area under the curve (AUC) to evaluate their screening accuracy. Results MAFLD had strong correlation with traditional BMI and new index LAP. ROC analysis showed that BMI had the highest AUC (0.89), followed by LAP (0.87). Stratification by BMI, LAP had the highest AUC (0.90) for MAFLD in population without obesity (BMI<23kg/m2), and its optimal cutoff value was 20.75, with a sensitivity and specificity of 85.9% and 79.0%, respectively. Conclusions We proposed a two-step screening strategy for MAFLD, combining BMI and LAP, and defined a high-risk population for MAFLD as follows: 1) BMI ≥23 kg/m2; and 2) BMI <23 kg/m2 and LAP ≥20.75.